2016
DOI: 10.1186/s40409-016-0066-7
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on the incidence of envenomation and accessibility to antivenom in Burkina Faso

Abstract: BackgroundSnakebite is a common neglected public health issue, especially in poor rural areas of sub-Saharan Africa, Asia and Latin America. Passive immunotherapy with safe and effective antivenom is the only approved treatment for it. This study aimed to determine the incidence of snakebites, and to assess the availability and accessibility of antivenoms, from 2010 to 2014, in Burkina Faso.MethodsThe assessment of snakebite cases managed in all health facilities from 2010 to 2014 was performed from the Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 6 publications
3
30
1
2
Order By: Relevance
“…We consistently found that young to middle-aged men (age group = 15-44 years) were most at risk of snakebites, corroborating similar findings from Ghana [22, 23, 24], other parts of West Africa [15, 25, 26, 27, 44, 46, 47] and Africa in general [30, 34, 48, 49, 50]. Adolescent and young men in their twenties are among the most active and adventurous, albeit least cautious, section of rural African people [24, 27, 44, 51]. They expose themselves to snake encounters by risky behaviour during land clearing, harvesting, bush and charcoal burning, hunting and commuting on foot during dark or early morning hours with impaired visibility in dim light and dense vegetation [24, 47, 50].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We consistently found that young to middle-aged men (age group = 15-44 years) were most at risk of snakebites, corroborating similar findings from Ghana [22, 23, 24], other parts of West Africa [15, 25, 26, 27, 44, 46, 47] and Africa in general [30, 34, 48, 49, 50]. Adolescent and young men in their twenties are among the most active and adventurous, albeit least cautious, section of rural African people [24, 27, 44, 51]. They expose themselves to snake encounters by risky behaviour during land clearing, harvesting, bush and charcoal burning, hunting and commuting on foot during dark or early morning hours with impaired visibility in dim light and dense vegetation [24, 47, 50].…”
Section: Discussionsupporting
confidence: 86%
“…With a large sample size of 1,024 respondents covering both dry and wet seasons, and a retrospective 10-year bivariate data sample of snakebite incidences and rainfall patterns, our study represents an important contribution to epidemiological snakebite studies for this region. Previous epidemiological studies have largely been limited to short-term data series with lower sample sizes of predominantly retrospective hospital records for Ghana [22, 23, 24] and sub-Saharan Africa [25, 26, 27, 28, 29], where complementary or nationwide long-term published studies remain scarce [1, 16, 30, 31]. Estimates of regional or national snakebite burdens based exclusively on hospital records inevitably neglect many snakebite cases treated at home or by TMPs [1, 4, 16, 30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Asia, some data exist in India, for example [ 8 ], but they do not suffice to bring a consistent view of the situation. Analyses of African data have indicated that the problem there is of much underestimated magnitude [ 9 ], and this is largely being confirmed by the first epidemiological analyses from national health registries [ 10 ].…”
mentioning
confidence: 99%
“…Data from studies conducted in India [11,14], Bangladesh [15], Sri Lanka [16,17], Nigeria [12,18], Burkina Faso [19], Kenya [20] and Senegal [21], amongst others, provide evidence of an increasing capability of acquiring snakebite epidemiology data that need to be adopted and promoted more widely. The workshop was informed of hospital-based and community survey projects being undertaken or planned in several countries represented by the recently established African Society of Venimology and in Southeast Asia.…”
Section: Priority Actions Identified and Progress To Meet The Retrmentioning
confidence: 99%